Fiscal Decentralization, Accountability and Corruption Indication: Evidence from Indonesia (Jurnal Bina Praja, 2021)
In the Corruption Perception Index 2019, Indonesia ranks 90th among 180 countries (Transparency International, 2020). Indonesia still among the lowest rank in the corruption index. This index shows that corruption is an important issue for Indonesia. Therefore, the study aims at examining the determinants of corruption in Indonesia. This study focuses on two important aspects: fiscal decentralization and accountability. Since the enactment of Law Number 22 of 1999, which was then revised by Law Number 32 of 2004, the local government can manage fiscal. It is expected that local governments can use resources for the improvement of the wealth of the citizens. Further, the local government has a responsibility for using the resources.  However, there are cases regarding corruption in local government in Indonesia. This study uses secondary data from local government financial statements to search the corruption indication, level of fiscal decentralization, and accountability. The study’s sample consists of 94 districts/cities on Java during the 2013-2015 period. The dependent variable in this study is an indication of corruption. Furthermore, the study divided corruption into three aspects: regional losses, potential regional losses, and revenue deficiency. The independent variables in this study were fiscal decentralization and accountability. This study uses multiple linear regression models to test the effect of fiscal decentralization and accountability on Indonesia’s corruption indicator. The result of the study shows that fiscal decentralization has a negative impact on corruption indication. The higher degree of fiscal decentralization minimizes the corruption indication in Java island. Meanwhile, fiscal decentralization has a negative effect on regional losses and revenue deficiency. Accountability has no significant on corruption indication. However, accountability has a negative impact on regional losses. In conclusion, both fiscal decentralization and accountability have curb corruption indication in the regional losses aspect.
Keywords: Indications of Corruption; Fiscal Decentralization; Accountability; regional losses; revenue deficiency